The Effectiveness of Methadone Maintenance Treatment in Controlling Crime: An Australian Aggregate-Level Analysis - Lind, Bronwyn; Chen, Shuling; Weatherburn, Don; Mattick, Richard (The British journal of criminology, 2005)
This article presents the results of a study into the effectiveness of methadone maintenance treatment in preventing crime. Using court appearance records, the officially recorded offending rates of a sample of 8,154 people on the public methadone programme between 1 January 1999 and 31 December 2000 were determined to see whether they were lower during periods when they were on the methadone programme than during periods when they were off the programme. After adjusting for time spent in custody, officially recorded offending rates were found to be significantly lower for most people during periods when they were in methadone treatment than during periods when they were out of it. A reduction in officially recorded offending rates was found for all age groups and for both men and women but the reduction was much more substantial for young women. When the reductions in officially recorded offending were scaled up to allow for offences that do not result in the prosecution of an offender, it was found that, for every 100 persons in methadone for one year, New South Wales gets 12 fewer robberies, 57 fewer break-and-enters and 56 fewer motor-vehicle thefts